2021
DOI: 10.1038/s41467-021-21559-9
|View full text |Cite
|
Sign up to set email alerts
|

Programmable C:G to G:C genome editing with CRISPR-Cas9-directed base excision repair proteins

Abstract: Many genetic diseases are caused by single-nucleotide polymorphisms. Base editors can correct these mutations at single-nucleotide resolution, but until recently, only allowed for transition edits, addressing four out of twelve possible DNA base substitutions. Here, we develop a class of C:G to G:C Base Editors to create single-base genomic transversions in human cells. Our C:G to G:C Base Editors consist of a nickase-Cas9 fused to a cytidine deaminase and base excision repair proteins. Characterization of >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 35 publications
(55 reference statements)
4
80
0
1
Order By: Relevance
“…However, C-to-T edits still predominated among the editing outcomes, suggesting room for improvement in achieving high C-to-G base editing purity by minimizing byproduct formation. Consistent with reports in human cell lines (Chen et al, 2021;Kurt et al, 2021;Zhao et al, 2021), these three CGBEs all greatly improved the ratios of C-to-G editing over C-to-T editing, as the control BE3 barely generated any C-to-G editing events in rice protoplasts (Figure 1) and tomato protoplasts (Figure 2). Such effects could be partly explained by the removal of UGI and addition of UNG or rXRCC1 (Chen et al, 2021;Kurt et al, 2021;Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, C-to-T edits still predominated among the editing outcomes, suggesting room for improvement in achieving high C-to-G base editing purity by minimizing byproduct formation. Consistent with reports in human cell lines (Chen et al, 2021;Kurt et al, 2021;Zhao et al, 2021), these three CGBEs all greatly improved the ratios of C-to-G editing over C-to-T editing, as the control BE3 barely generated any C-to-G editing events in rice protoplasts (Figure 1) and tomato protoplasts (Figure 2). Such effects could be partly explained by the removal of UGI and addition of UNG or rXRCC1 (Chen et al, 2021;Kurt et al, 2021;Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with reports in human cell lines (Chen et al, 2021;Kurt et al, 2021;Zhao et al, 2021), these three CGBEs all greatly improved the ratios of C-to-G editing over C-to-T editing, as the control BE3 barely generated any C-to-G editing events in rice protoplasts (Figure 1) and tomato protoplasts (Figure 2). Such effects could be partly explained by the removal of UGI and addition of UNG or rXRCC1 (Chen et al, 2021;Kurt et al, 2021;Zhao et al, 2021). Evaluation of editing windows for these three CGBEs in rice and tomato protoplasts showed editing preference for C6 in the 20-nucleotide target sequence, which is a general feature reported for CGBEs (Chen et al, 2021;Kurt et al, 2021;Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Our OPTI-CGBEs outperformed previously reported CGBE1 6 and prime editors 15 , 16 in C-to-G editing efficiency and product purity across the tested target sites. Very recently, Chen et al reported a C-to-G base editor by replacing the UGI of BE3 with base excision repair (BER) proteins with improved C-to-G editing efficiency at specific motifs 30 . Notably, in our study we found that OPTI-CGBEs differ from corresponding CBEs in their motif preferences, and CGBEs with deaminases of different origins prefer distinct sequence context.…”
Section: Discussionmentioning
confidence: 99%
“…The clever combination of engineered molecular biology components results in a number of advantages, in addition to high efficiency of editing by single base substitution. Whilst their previous BE strategies provided a mechanism of creating single base substitutions for the four transitions (C > T; T > C; A > G; G > A), and recent studies have expanded this to include two transversions (C > G and G > C [ 3 5 ]), PE encompasses all potential 12 modifications including the eight transversions. This provides a much swifter process for developing therapeutic editing for any disease caused by a single base pair change, as well as the potential for researchers to model any SNP in vitro.…”
Section: Back To Basics – the Operational Components Of Pementioning
confidence: 99%